Heidelberg Radiocarbon Lab: establishing a new carbon dioxide extraction line for carbonate samples - Therre, Steffen; Proß, Lukas; Friedrich, Ronny; Trüssel, Martin; Frank, Norbert (Radiocarbon, 2021)
To achieve high-precision and reproducible results from radiocarbon (14C) dating of carbonate samples in paleoclimate research, a new CO2 extraction line was designed, constructed, and characterized at the Heidelberg Radiocarbon Lab of the Institute of Environmental Physics, Heidelberg. The setup includes a circular glass-tube design, which is operated at vacuum pressure levels of the order of 10-5 mbar. The efficiency of the extraction process was assessed, showing significantly favorable conditions for solid piece samples (99.58 ± 4.69)% over powdered samples (88.28 ± 10.03)%. Process blank values are below 0.2 pMC apparent 14C activity. Repeated measurements of IAEA C2 standards with an average value of (41.09 ± 0.23) pMC attest high accuracy and reproducibility of the instrument. Six consecutive samples of 6 to 12 mg carbonate mass can be processed in one run of roughly 2.5 hours. Thus, the new setup contributes to time-efficient and reproducible radiocarbon dating results for paleoclimate research at the Institute of Environmental Physics. In a first application, Dead Carbon Fraction (DCF) values of a Holocene alpine stalagmite from Schratten Cave are presented, revealing extraordinarily high offsets between atmospheric and stalagmite 14C with DCF values between (49.4 ± 0.4)% and (61.6 ± 0.4)%.
Gesehen am 27.06.2022